2000
DOI: 10.1099/0022-1317-49-10-897
|View full text |Cite
|
Sign up to set email alerts
|

Infection of human enterocyte-like cells with rotavirus enhances invasiveness of Yersinia enterocolitica and Y. pseudotuberculosis

Abstract: Mixed infection with rotavirus and either Yersinia enterocolitica or Y. pseudotuberculosis was analysed in Caco-2 cells, an enterocyte-like cell line highly susceptible to these pathogens. Results showed an increase of bacterial adhesion and internalisation in rotavirus-infected cells. Increased internalisation was also seen with Escherichia coli strain HB101 (pRI203), harbouring the inv gene from Y. pseudotuberculosis, which is involved in the invasion process of host cells. In contrast, the superinfection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…The unchanged ␣5 expression at 8 h p.i. observed in this study confirms the previous report that ␣5 is unaltered at this time (21). The kinetics of integrin regulation in Caco-2 cells infected with CRW-8 or RRV were indistinguishable (data not shown).…”
Section: Rotavirus Replication In Intestinal Cells Led To Differentiasupporting
confidence: 82%
See 1 more Smart Citation
“…The unchanged ␣5 expression at 8 h p.i. observed in this study confirms the previous report that ␣5 is unaltered at this time (21). The kinetics of integrin regulation in Caco-2 cells infected with CRW-8 or RRV were indistinguishable (data not shown).…”
Section: Rotavirus Replication In Intestinal Cells Led To Differentiasupporting
confidence: 82%
“…(21). Microarray analysis showed that levels of ␣2, ␣6, and ␤1 integrin subunit mRNA increased 3.1-, 2.7-, and 2.8-fold, respectively, in rhesus monkey rotavirus (RRV)-infected Caco-2 cell cultures at 16 h p.i., compared with levels in mock-infected cells (19).…”
mentioning
confidence: 99%
“…Viral and bacterial intestinal pathogens could affect either the same or different regions of the gut, and their effects would be enhanced (11). Mixed infections have been described previously in children with acute gastroenteritis, but few data on the role of noroviruses in dual infections are available.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, viral and bacterial intestinal pathogens could affect either the same or different regions of the gut, and their effects would be enhanced (Di Biase et al, 2000). Currently, we still know little about the exact pathology of human gut infections, and it is useful to report studies which examine both viruses and bacteria.…”
Section: E Romá N and Others 438mentioning
confidence: 99%